Pengaruh Biblioterapi “Teruslah Semangat Nadi” terhadap Stres Hospitalisasi Anak Pra Operasi - Nadhya Ayuningtyas; Aprina Aprina; Anita Anita (Jurnal Kesehatan, 2020)
Profile of Indonesian Children in Ministry Of Women Empowerment and Child Protection (2018), in 2017, children aged 0-17 years were diagnosed with a health complaint were 28,56%, while sick children (morbidity) were 15,86%. There is a need for psychological support so that children do not experience hospitalization stress by using storybooks that are constructive and optimistic to reduce stress on children in available health facilities. For a similarity between the child's condition and the content and meaning contained therein, the researcher used a storybook where there are similarities between hospitalized children and the contents of the story so that children can easily understand the contents of the story, this book is entitled "Teruslah Semangat Nadi". Pre survey data obtained data on the incidence of surgery for the last 3 months, some children cried when they were about to undergo nursing actions, asked to go home, had difficulty sleeping, etc. by 80%. This type of quantitative research uses a quasi-experimental research method and a One Group Pretest Post-test research design. Non-random sampling data collection technique with accidental sampling approach. The sample of this research is children aged at least 5 years as many as 30 respondents. The research analysis used a statistical test with a dependent t-test. Result this study is p-value 0,000 (α<0,05). There is an effect of bibliotherapy "Teruslah Semangat Nadi" on the stress of preoperative child hospitalization in Dr. H. Abdul Moeloek, Lampung Province in 2020.